Memahami Kompleksitas Transformasi Agama-agama di Jawa melalui Teks - Agus Iswanto (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2018)
Book Review: Yumi Sugahara dan Willem van der Molen (editor), Transformation of Religions as Reflected in Javanese Texts, Tokyo: Research Institute for Languages and Cultures of Asia and Africa Tokyo University of Foreign Studies. 2018.